Circulating GLAST+ EVs are increased in amyotrophic lateral sclerosis - Raineri, Davide; De Marchi, Fabiola; Vilardo, Beatrice; Barbero Mazzucca, Camilla; Scotti, Lorenza; Kustrimovic, Natasa; Mazzini, Letizia; Cappellano, Giuseppe; Chiocchetti, Annalisa (Frontiers in Molecular Biosciences, 2024)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder, hallmarked by the gradual deterioration of motor neurons, culminating in muscle weakness and fatal paralysis. The exact etiology of ALS remains elusive, and there is a critical need for reliable biomarkers to aid in diagnosis and monitoring of disease progression. Extracellular vesicles (EVs) have emerged as promising candidates for biomarker discovery in neurodegenerative diseases such as ALS, giving access to pathologically relevant tissues otherwise typically challenging or invasive to sample. Indeed, EVs can derive by many cell types within the central nervous system, cross the blood-brain barrier and reach the blood, where they can be easily measured. One of the central mechanisms implicated in ALS pathology is glutamate excitotoxicity, which involves excessive glutamate accumulation due to impaired uptake by astrocytes and other glial cells, leading to neuronal damage. GLAST is a key glutamate transporter responsible for maintaining extracellular gluta-mate levels, and its dysregulation is thought to contribute significantly to ALS development and associated neuropathogenesis. Here, we applied a quick and validated method, to evaluate GLAST+ EVs in ALS patients’ plasma and age-matched healthy controls. We found an increase in GLAST+ EVs that holds promise for uncovering novel diagnostic and therapeutic avenues in ALS research.